Role of the Arachidonic Acid Cascade in the Expression of Withdrawal Signs in Alcohol Dependent Mice: - Kusnandar Anggadireja; Razana Bt. Adam Lee (School of Pharmacy Institut Teknologi Bandung, 2021)
Withdrawal symptom in alcohol dependence is one the main problems in treating alcohol addiction. This study was aimed to clarify the role of the arachidonic acid cascade in the expression of withdrawal signs in animal model of alcohol dependence. Dependence was induced by repeated administration of 15% ethanol in 0.2% sucrose solution for 17 days. On the 18th day, the ethanol was not given, and one hour after the supposed time of ethanol administration, diclofenac at 10 mg/kg was injected i.p. to induce withdrawal. Observation of behavioral withdrawal signs was performed for 30 minutes, starting 25 minutes after diclofenac injection. Following behavioral observation, forced swimming test ensued to assess depression during withdrawal. In different group of mice, ibuprofen at 7.5 mg/kg was given every other day during ethanol regimen, 30 minutes prior to ethanol. Results showed that diclofenac induced the expression of withdrawal signs in mice receiving repeated alcohol. Incidences of facial preening (P<0.01), forepaw licking (P<0.01), grooming (P<0.01) and forepaw tremor (P<0.001) increased significantly by at least three times the normal value. In mice pretreated with ibuprofen significant decreases in body weight reduction (300%, P<0.01) and immobility time (50%, P<0.05) were observed compared to that of ethanol group. Taken together, the data indicates that suppressed arachidonic acid cascade signaling is involved in the expression of alcohol withdrawal.